Efficiency of a pilot-plant for the autothermal reforming of biogas. (19th July 2019) - Rau, F.; Herrmann, A.; Krause, H.; Fino, D.; Trimis, D.
Abstract: A grid of hydrogen refuelling stations comparable to gasoline is essential for improving the individual transport based on fuel cell technology. To avoid transport and storage problems with hydrogen, small-scale hydrogen production plants are required. During the project BioRobur a pilot-plant with a hydrogen output of 50 Nm³/h was constructed and investigated. The plant is based on the autothermal reforming of biogas with a noble metal catalyst. All required reactants are stored or produced at the plant side. The purification of the synthetic gas is not considered. Within the article the plant efficiency and the cold gas efficiency were measured at different temperatures, oxygen to carbon ratios and gas hourly space velocities. Additionally the workload of the pilot-plant was varied, showing a highly reliable operation for a workload of at least 20%. Furthermore, the hydrogen production costs of the pilot-plant were compared with other common technologies, like electrolysis and steam reforming. Highlights: Autothermal reforming of biogas at pilot-plant. Highest plant efficiency of 75% at an O/C-ratio of 0.8–0.9. Partial load operation down to 20%. Production costs are 0.16 €/kWh (5.32 €/kg).